How to land a job in an international organization abroad (for secretaries and other occupations) - Peralta, Tina (Quezon City Great Books, 1991)
Purpose: Provides a systematic and practical approach on how to land a job abroad or in the country.
Content/s: International Organization. International Secretary. Qualifications. Job Content. Skills Audit. Pre-departure Planning and Preparation. Travel Checklist. Employment Interview. Employment and Living Conditions. Fixed-Term Contract.
Title from cover.
Keywords: Job hunting -- Philippines -- Handbooks, manuals, etc; Occupations; Vocational guidance -- Philippines -- Handbooks, manuals, etc